Vertebral Compression Fracture Related to Pancreatic Cancer With Osteoblastic Metastasis: A Case Report and Literature Review. Issue 5 (February 2016) - Chih, Yu-Pin; Wu, Wei-Ting; Lin, Chien-Lin; Jou, Herng-Jeng; Huang, Yu-Hsuan; Chen, Liang-Chi; Chou, Li-Wei
Abstract : Abstract: Compression fracture of the vertebral body is common in the older patients. The possible etiology like osteoporosis or cancer metastasis should be included as a possibility in the differential diagnosis for severe back pain, to prevent delays in diagnosis and treatment. More severe fractures can cause significant pain, leading to inability to perform activities of daily living, and life-threatening in the older patient. We report a rare case of a 61-year-old man suffering from severe lower back pain and intermittent abdominal fullness. He came to our clinic, where muscle power was normal, but could not stand up or change posture because of severe back pain. Plain film and magnetic resonance imaging of lumbar spine both revealed osteoblastic lesion at L2 spine. Abdomen computed tomography showed a mass at the pancreatic body. The pancreatic cancer with osteoblastic metastasis was diagnosed. After receiving multimodality therapy such as percutaneous vertebroplasty and pain controlling, we provided effective palliation of symptoms, aggressive rehabilitation program, and better quality of life. Our case highlights the benefits of multidisciplinary cancer treatment for such patient, preventing the complications such as immobilization accompanied with adverse effects like musculoskeletal, respiratory, and cardiovascular systems. All clinicians should be informed of the clinical findings to provide patients with suitable therapies and surveys.